Tata Kelola Koperasi Syariah di Indonesia : Studi Literatur Review - Iswandi, Andi (Al-Tasyree: Jurnal Bisnis, Keuangan dan Ekonomi Syariah, 2023)
This study comprehensively evaluates the implementation of governance in Sharia cooperatives in Indonesia, focusing on decision-making, transparency, and justice. In the context of rapid economic growth, Sharia cooperatives are expected to be an alternative financial pillar, adhering to Sharia principles and promoting economic justice and sustainability. However, previous research has identified several obstacles, including a lack of transparency, low member participation, challenges in implementing Sharia principles, and structural issues. In-depth literature reviews, such as those by Wahyudin et al. (2022) and Nurhidayati (2018), cover the dimensions of Sharia cooperative governance, highlighting crucial factors affecting governance quality. This study employs a descriptive analytical method, collecting data from literature, official documents, and recent publications. The analysis indicates that many Sharia cooperatives have not fully implemented effective governance, requiring improvements in transparency, member participation, Sharia principle application, and structural enhancements. The conclusion emphasizes the urgency of improving the quality of Sharia cooperative governance to effectively contribute to sustainable and inclusive economic development in Indonesia. The implications of this research involve recommendations for enhancing Sharia cooperative governance, providing valuable guidance for stakeholders, and enriching scholarly literature in the fields of cooperatives and Sharia economics.